Intracoronary epinephrine versus adenosine in the management of refractory no-reflow phenomenon: a single-center retrospective cohort study - Ahmed Darwish; Abdel-Fattah Frere; Magdy Abdelsamie; Waleed El Awady; Mohammad Gouda (Annals of Saudi Medicine)
BACKGROUND: The no-reflow phenomenon is associated with a considerable reduction in myocardial salvage in patients with ST elevation myocardial infarction (STEMI) treated by primary percutaneous intervention (PCI). There has been no head-to-head comparison of intra-coronary epinephrine to adenosine in the management of no-reflow phenomenon. OBJECTIVES: Evaluate the short- and long-term efficacy and safety of using intracoronary epinephrine versus adenosine for management of the catastrophic no-reflow phenomenon that may occur during primary PCI. DESIGN: Retrospective cohort. SETTING: Single center in Egypt. PATIENTS AND METHODS: The study included STEMI patients who developed refractory no-reflow phenomenon during primary PCI after failure of conventional treatments and received either intracoronary epinephrine or adenosine. MAIN OUTCOME MEASURES: No-reflow management measured through improvement of thrombolysis in myocardial infarction grade (TIMI flow), myocardial blush grade, TIMI frame count and major adverse cardiovascular events (MACE) at 1-year follow up. SAMPLE SIZE: 156 patients with refractory no-reflow phenomenon during primary PCI. RESULTS: Successful reperfusion was achieved in 74 of 81 (91.4%) of patients who received epinephrine and in 65 of 75 (86.7%) who received adenosine (P<.05). Fifty-six of 81 patients (69.1%) achieved TIMI III flow after epinephrine administration versus 39 of 75 patients (52.7%) in the adenosine group (P=.04). The incidence of heart failure after 1 year of follow up was lower in the epinephrine group compared to the adenosine group (6.3% vs. 19.2%, P<.017). MACE after 1 year of follow up was lower in patients who received epinephrine compared to those who received adenosine (11.3 % Vs. 26.7 %, P<.01). CONCLUSION: During primary PCI, intracoronary epinephrine is as effective as adenosine in successful management of refractory no-reflow phenomenon with a more favorable long-term prognosis compared to adenosine. LIMITATIONS: Retrospective design. CONFLICT OF INTEREST: None.